Ice hockey coaches` perceptions of their role in supporting athlete mental health - Henderson, S.; Bloom, G. A.; Heath, N. L. (International Sport Coaching Journal, 2026)
Many coaches have reported not feeling well equipped to support and discuss mental health issues with their athletes. The purpose of this study was to understand elite ice hockey coaches` perceptions of their role in supporting athlete mental health, along with their experiences in taking part in a mental health and suicide awareness program. Five coaches of elite 16- to 20-year-old ice hockey players who had taken part in a mental health and suicide awareness program for at least one season each participated in an individual, semistructured, open-ended interview. Data were analyzed using a reflexive thematic analysis. Results revealed that coaches perceived their role to entail integrating mental health considerations into their daily coaching practices, paying attention to signs of player distress, assessing risk in various situations, and referring players to health professionals when necessary. Overall, our findings offered insight into coaches` perceived role in providing mental health support to athletes, as well as helping to identify strengths and areas to improve the mental health and suicide awareness program. Consequently, coaches are primed to be key players in helping to create a sport climate in which well-being is prioritized and is perceived as a catalyst to performance.